An unusual presentation of Kabuki syndrome with orbital cysts, microphthalmia, and cholestasis with bile duct paucity. Issue 12 (17th August 2016) - Bögershausen, Nina; Altunoglu, Umut; Beleggia, Filippo; Yigit, Gökhan; Kayserili, Hülya; Nürnberg, Peter; Li, Yun; Altmüller, Janine; Wollnik, Bernd
Abstract : Kabuki syndrome (KS) is a rare developmental disorder characterized by multiple congenital malformations, postnatal growth retardation, intellectual disability, and recognizable facial features. It is mainly caused by mutations in either KMT2D or KDM6A . We describe a 14‐year‐old boy with KS presenting with an unusual combination of bilateral microphthalmia with orbital cystic venous lymphatic malformation and neonatal cholestasis with bile duct paucity, in addition to the typical clinical features of KS. We identified the novel KMT2D mutation c.10588delC, p.(Glu3530Serfs*128) by Mendeliome (Illumina TruSight One®) sequencing, a next generation sequencing panel targeting 4, 813 genes linked to human genetic disease. We analyzed the Mendeliome data for additional mutations which might explain the exceptional clinical presentation of our patient but did not find any, leading us to suspect that the above named symptoms might be part of the KMT2D ‐associated spectrum of anomalies. We thus extend the range of KS‐associated malformations and propose a hypothetical connection between KMT2D and Notch signaling. © 2016 Wiley Periodicals, Inc.